Evolutions of Oil Generation and Expulsion of Marine-Terrestrial Transitional Shales: Implications From a Pyrolysis Experiment on Water-Saturated Shale Plunger Samples - Fan, Qizhang; Cheng, Peng; Xiao, Xianming; Gai, Haifeng; Zhou, Qin; Li, Tengfei; Gao, Ping (Frontiers in Earth Science, 2021)
Shale oil and gas reservoirs are characterized by self-generation and self-accumulation. The oil generation and expulsion evolution model of organic-rich shales has obvious influences on the enrichment and accumulation of shale oil and gas resources. Previous relevant researches mainly focused on marine and lacustrine shales, while few of studies have performed on marine-terrestrial transitional shales. In this study, water-saturated marine-terrestrial transitional shale plunger samples with type-Ⅱb kerogen were used for a pyrolysis experiment, to simulate the evolutions of oil generation and expulsion. The results indicate that the marine-terrestrial transitional shale has much wider maturity ranges of oil generation and expulsion than the marine and lacustrine shales, and the main stages of oil expulsion are much later than those of oil generation, with the corresponding Ro values of 0.85–1.15% and 0.70–0.95% respectively. The oil generation and expulsion induced a fractionation in compositions between the expelled and retained oils. However, the two types of oils are dominated by heavy compositions (resin and asphaltenes), which significantly differs from the marine and lacustrine shales. The oil generation and expulsion evolutions of marine-terrestrial transitional shales are largely determined by their organic sources, which are mainly contributed from terrigenous higher organisms. The kerogen of the studied shale cracked into hydrocarbons via initially depolymerizing to transitional asphaltenes. Meanwhile, the weak kerogen swelling effects of this shale probably are the main mechanism accounting for its high oil expulsion efficiency. The oil generation and expulsion model obtained in this study provides a theoretical basis to understand the enrichment mechanism of marine-terrestrial transitional shale oil and gas resources.